Genome-wide association analysis of 95 549 individuals identifies novel loci and genes influencing optic disc morphology. (6th September 2019) - Han, Xikun; Qassim, Ayub; An, Jiyuan; Marshall, Henry; Zhou, Tiger; Ong, Jue-Sheng; Hassall, Mark M; Hysi, Pirro G; Foster, Paul J; Khaw, Peng T; Mackey, David A; Gharahkhani, Puya; et al.
Abstract: Optic nerve head morphology is affected by several retinal diseases. We measured the vertical optic disc diameter (DD) of the UK Biobank (UKBB) cohort ( N = 67 040) and performed the largest genome-wide association study (GWAS) of DD to date. We identified 81 loci (66 novel) for vertical DD. We then replicated the novel loci in International Glaucoma Genetic Consortium (IGGC, N = 22 504) and European Prospective Investigation into Cancer–Norfolk ( N = 6005); in general the concordance in effect sizes was very high (correlation in effect size estimates 0.90): 44 of the 66 novel loci were significant at P < 0.05, with 19 remaining significant after Bonferroni correction. We identified another 26 novel loci in the meta-analysis of UKBB and IGGC data. Gene-based analyses identified an additional 57 genes. Human ocular tissue gene expression analysis showed that most of the identified genes are enriched in optic nerve head tissue. Some of the identified loci exhibited pleiotropic effects with vertical cup-to-disc ratio, intraocular pressure, glaucoma and myopia. These results can enhance our understanding of the genetics of optic disc morphology and shed light on the genetic findings for other ophthalmic disorders such as glaucoma and other optic nerve diseases.